Multiple Intelligences Strategies, Students’ Motivation, Reading Comprehension - Afriyanti (Journal of Innovative and Creativity, 2022)
The study discusses about improving students’ motivation on reading comprehension by using Multiple Intelligences strategies. The objectives of the study are explaining 1) the problems faced by the eight graders of SMP 3 Bonai Darusalam, Rokan Hulu in reading comprehension, 2) the implementation of Multiple Intelligences strategies in motivating reading comprehension for the eight graders of SMP 3 Bonai Darusalam, Rokan Hulu, Riau, 3) how Multiple Intelligences strategies improve the motivation of the eight graders of SMP 3 Bonai Darusalam, Rokan Hulu in reading comprehension. In order to achieve the objectives, the researcher held an action research at SMP 3 Bonai Darusalam, Rokan Hulu on 16th of March- 9th April 2022. There were 2 cycles in which 2 meetings held for each cycle. The subject of the study is the second graders of SMP 3 Bonai Darusalam, Rokan Hulu. The numbers of population are 32 students. The instruments used were observation sheet, questionnaire, and CARI. The result of the study is the problem in motivating students to read. This can be solved by using Multiple Intelligences strategies which combine students’ intelligences with fun learning activities by Multiple Intelligence instruction. Based on the questionnaire, all of the students said that the strategies used were interesting. In line with the questionnaire result, the observation sheet also showed excellent result on students’ study habits. There was improvement on students’ comprehension, it can be seen from the mean of CARI I which was 89.06 point and CARI II which was 95.6 point. In this study, I suggest that the teachers should be able to use the Multiple Intelligences strategies as an alternative in motivating students and creating enjoyable learning experiences.